Desenvolvimento e validação de atlas virtual de peças anatômicas 3D obtidas por fotogrametria: estudo randomizado controlado - Freitas, Jônatas Catunda de (2024)
INTRODUCTION: The scarcity of anatomical specimens is a growing issue in medical education, limiting students' access to essential resources for practical anatomy learning. Photogrammetry, a technology that creates 3D digital models from photographs of objects, has been used in anatomical studies. However, to date, no atlas or application that includes real 3D scanned anatomical specimens has been developed. OBJECTIVES: To develop and validate an online 3D virtual anatomy atlas platform, free of charge and comprised of 3D scanned anatomical specimens from cadavers, as an innovative and accessible educational tool for teaching anatomy. METHODOLOGY: The methodology involved developing a virtual atlas, standardizing photogrammetry for digitizing anatomical pieces, and conducting a validation study with medical students to test the effectiveness of the virtual atlas as an educational tool. Rigorous criteria were applied in development, including usability, security, bioethics, and a collaborative model. A randomized controlled trial was conducted to compare a control group with an experimental group that had early access to the platform during the cardiorespiratory system discipline. The anatomy exam scores of both groups were compared. RESULTS: The virtual atlas was developed, and photogrammetry using smartphone apps was standardized, resulting in the creation of 27 digital models from anatomical pieces. A total of 168 students participated in the validation study. The results revealed that the virtual atlas, through its digital repository of anatomical pieces, significantly enhanced student engagement and performance compared to traditional methods. The experimental group showed superior performance in the practical anatomy exam, with an average score of 8.4 ± 1.4 compared to 7.9 ± 1.5 for the control group, with a p-value of 0.027. CONCLUSION: The virtual atlas was successfully developed and validated, proving to be an innovative and accessible educational tool that enhances the teaching of anatomy through three-dimensional digital resources.